Experimental measurement-based quantum computing beyond the cluster-state model - Gao, Wei-Bo; Yao, Xing-Can; Cai, Jian-Ming; Lu, He; Xu, Ping; Yang, Tao; Lu, Chao-Yang; Chen, Yu-Ao; Chen, Zeng-Bing; Pan, Jian-Wei (Nature photonics, 2011)
The paradigm of measurement-based quantum computation opens new experimental avenues to realizing a quantum computer, and also deepens our understanding of quantum physics. Measurement-based quantum computation originates with a highly entangled universal resource state. For years, clusters states have been the only known universal resources. Surprisingly, a novel framework, namely quantum computation in correlation space, has opened a new route to implementing measurement-based quantum computation based on quantum states having entanglement properties, which differ from cluster states. Here, we report an experimental demonstration of every building block of such a model. With four-qubit and six-qubit states, which are not in the cluster-state category, we have realized a universal set of single-qubit rotations, two-qubit entangling gates and also Deutsch's algorithm. As well as being of fundamental interest, our experiment proves, in principle, the feasibility of universal measurement-based quantum computation without the use of cluster states, which represents a new approach towards the realization of a quantum computer.
Gesehen am 17.07.2023